2005
DOI: 10.1038/nm1278
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones expand body fluid volume through PPARγ stimulation of ENaC-mediated renal salt absorption

Abstract: Thiazolidinediones (TZDs) are widely used to treat type 2 diabetes mellitus; however, their use is complicated by systemic fluid retention. Along the nephron, the pharmacological target of TZDs, peroxisome proliferator-activated receptor-gamma (PPARgamma, encoded by Pparg), is most abundant in the collecting duct. Here we show that mice treated with TZDs experience early weight gain from increased total body water. Weight gain was blocked by the collecting duct-specific diuretic amiloride and was also prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
496
7
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(519 citation statements)
references
References 35 publications
7
496
7
9
Order By: Relevance
“…Shortterm animal studies also show that there is a rapid increase in body weight during the first week of treatment, clearly due to an increase in water content [6,7] and an increase in the epithelial sodium channel (ENaC) activity. These effects were inhibited by amiloride, an ENaC inhibitor, and abolished in mice with specific deletion of the collecting duct PPAR-γ suggesting an important role of glitazoneinduced sodium retention through ENaC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortterm animal studies also show that there is a rapid increase in body weight during the first week of treatment, clearly due to an increase in water content [6,7] and an increase in the epithelial sodium channel (ENaC) activity. These effects were inhibited by amiloride, an ENaC inhibitor, and abolished in mice with specific deletion of the collecting duct PPAR-γ suggesting an important role of glitazoneinduced sodium retention through ENaC.…”
Section: Discussionmentioning
confidence: 99%
“…Both direct and indirect effects of glitazones on renal sodium reabsorption have been proposed, through the direct activation of tubular peroxisome proliferator-activated receptor (PPAR)-γ or indirectly through the activation of compensatory mechanisms secondary to the glitazone-induced vasodilation [6][7][8]. Experimental studies have shown that glitazones may increase sodium transport in the proximal convoluted tubules, the thick ascending limb and the collecting duct [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The latter, which can be explained by PPARg stimulation of ENaC-mediated renal salt absorption [218], might be the cause of an increased incidence of congestive heart failure [219], an outcome also observed in rats where rosiglitazone treatment is associated with increased post-myocardial infarction mortality [220]. However, this issue is still under debate as the Prospective Pioglitazone Clinical Trial in Macrovascular Events (PROactive) showed recently that treatment of type 2 diabetic patients with pioglitazone, another TZD drug, improved their cardiovascular outcome [113].…”
Section: Use Of Synthetic Pparg Agonists In the Treatment Of Lipodystmentioning
confidence: 99%
“…SPPARgMs would separate the effects of PPARg on lipid and glucose metabolisms as well as on different organ systems (gastrointestinal, immune, cardiovascular). The selective action of such compounds is thought to depend on different structural configurations induced in the ligand-binding domain by their interaction with the receptor, allowing recruitment of different complexes of cofactors that impact on the activation or repression of specific sets of target genes in different tissues [146,218,[226][227][228][229][230][231].…”
Section: Selective Pparg Modulators: a Better Alternative?mentioning
confidence: 99%
“…On the one hand, PPARγ agonists were found to upregulate mRNA levels of SCNN1G encoding for the gamma subunit of ENaC in a mouse inner medullary collecting duct cell line [19]. On the other hand PPARγ agonists have been shown to stimulate the transcription of the serum and glucocorticoid-inducible kinase SGK1 [22], which, in turn, was suggested to enhance the surface expression of ENaCα [22].…”
Section: Introductionmentioning
confidence: 99%